2014
DOI: 10.1111/psyp.12230
|View full text |Cite
|
Sign up to set email alerts
|

Frontal EEG asymmetry as predictor of physiological responses to aversive memories

Abstract: Evidence suggests that asymmetry in frontal electrical activity predicts responses to aversive experiences, such that higher left-sided activity might dampen responses to trauma reminders. We measured frontal asymmetry at rest and during viewing of a trauma film, and assessed startle responses to film-reminder images. To explore potential moderators, we compared two films (Study 1; N = 64) and modulated reappraisal (Study 2; N = 72). As expected, left frontal activation during film viewing predicted dampened r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…Another finding that may inspire future research is that trauma‐exposed participants with stronger left‐sided frontal activity at rest displayed more emotionally intense traumatic memories, and that left‐sided activation asymmetry during neutral picture viewing tended to correlate with higher arousal levels immediately following an intrusion. These results appear to contravene the overall pattern in our results (i.e., left‐sided frontal activity predicting fewer PTSD symptoms), yet they align with the finding that left‐sided activity can be associated with both stronger and weaker physiological downregulation of affective responses (e.g., Meyer et al, ). Indeed, both the left and right hemispheres can be involved in increases and decreases of autonomic nervous system and stress hormonal responses (Kline, ; Miller, Crocker, Spielberg, Infantolino, & Heller, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Another finding that may inspire future research is that trauma‐exposed participants with stronger left‐sided frontal activity at rest displayed more emotionally intense traumatic memories, and that left‐sided activation asymmetry during neutral picture viewing tended to correlate with higher arousal levels immediately following an intrusion. These results appear to contravene the overall pattern in our results (i.e., left‐sided frontal activity predicting fewer PTSD symptoms), yet they align with the finding that left‐sided activity can be associated with both stronger and weaker physiological downregulation of affective responses (e.g., Meyer et al, ). Indeed, both the left and right hemispheres can be involved in increases and decreases of autonomic nervous system and stress hormonal responses (Kline, ; Miller, Crocker, Spielberg, Infantolino, & Heller, ).…”
Section: Discussionsupporting
confidence: 88%
“…These results appear to contravene the overall pattern in our results (i.e., left-sided frontal activity predicting fewer PTSD symptoms), yet they align with the finding that leftsided activity can be associated with both stronger and weaker physiological downregulation of affective responses (e.g., Meyer et al, 2014a). Indeed, both the left and right hemispheres can be involved in increases and decreases of autonomic nervous system and stress hormonal responses (Kline, 2017;Miller, Crocker, Spielberg, Infantolino, & Heller, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…It is likely that cognitive processes significantly impact rLFA (Papousek & Schulter, 2004) and individuals with less rLFA REZNIK AND ALLEN | 3 of 32 may have more impaired reasoning in depression (Brzezicka, Kami nski, Kami nska, Woły nczyk-Gmaj, & Sedek, 2016). For example, Meyer et al (2014) found a significant difference in response to two trauma-related films that differed in their difficulty of cognitive reappraisal. Therefore, it may be important to consider the degree to which a task constrains cognition.…”
Section: Methodological Issues In Frontal Asymmetry Researchmentioning
confidence: 99%
“…This film was well suited for the purpose of this study, as it was rich in distinctive features such as multiple victims of varying age, rescue helicopters and short dialogues. Prior studies have successfully used this material to induce negative affect (NA) and aversive memories (Meyer et al, ; Meyer et al, ).…”
Section: Methodsmentioning
confidence: 99%